Economia monetária: Análise da Bitcoin como dinheiro, tecnologia e mitigador de riscos - Belem, Joao Vitor da Costa (2022)
This work will approach Bitcoin as an alternative for ordinary money in order to observe the many different functions, peculiarities and efficiency of each type of money, as well as exploring the Blockchain technology and what it can mean for the future not only of cryptocurrencies, but of the whole economy. For this, the work will rely on a historical-economic analysis of money, aiming to analyze how and what types of money stood out, how the State was gradually assuming a key role over money and how this influenced the emergence of cryptocurrencies as an alternative to centralization of currency issuance. Furthermore, an investigation will be conducted using an econometric model to analyze the properties of Bitcoin as a risk mitigator compared to other assets, especially considering the COVID-19 pandemic. In view of the above, it is necessary to investigate how it works and how we reached this point in the evolution of money, based on history and data, since money is a fundamentally social phenomenon, supported by current social relations